Edukasi Pembelajaran dalam Pengolahan Sampah dan Latihan Menabung bagi Siswa Sekolah Dasar di Dusun Nambongan - Dyah Herdiany, Hapsari; Nindya Aryandha, Pradita; Putranti, Latifah; Imam Basri, Anindita; Sudaryana, Arif; Ardita Febriana, Elsa; Yuli Rahayu, Puput; Khairunnisa, Tiara; Nur Samsiah, Fitriana (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Community service activities are activities that aim to help the community in various aspects without expecting anything in return. The target of the community service activities that the author carried out has a focus on increasing knowledge and training skills. The author carried out community service activities after seeing the problems and conditions of the service location environment. The service location environment has a large number of children and there are no programs targeting children. In addition, the current condition of children is less understanding of waste management and the importance of saving. At the service location, children tend to ignore waste and saving because the majority already use cellphones in their daily activities. Seeing these problems, the author carried out community service activities with the title of training in making piggy banks from used materials and socializing waste management. Participants in the activity were enthusiastic in participating in the activities as evidenced by the active participation of participants in discussion activities and the results of work and creativity that emerged from the participants.